HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA REALISTIK DI KELAS IV SD NEGERI 195 ISOLA KOTA BANDUNG - Yanti Rohmani Hidayat; Linda Hania Fasha (COLLASE (Creative of Learning Students Elementary Education), 2021)
AbstractThis research was motivated by the low number of students completing the minimum skills in mathematics. This research also was motivated by the students’ below average achievements, which could be affected by the way teachers teach mathematics, who tend to only teach basic skills, such as standard addition, subtraction and remembering mathematical formulas which are very abstract, whereas primary school students have concrete mindset. Therefore, I believe that by using the Realistic Mathematics Education (RME) approach could help students to expand and explore their concrete mindset. The method that I will be using for my research is qualitative descriptive. The subjects for this research are grade 4 students of SD Negeri 195 Isola, Bandung. These students are from grade 4A consisting of 17 male students and 24 female students. The data are collected using various methods, including interviews, observations, teaching and learning documentation, tests and surveys. Based on the data collected, there are few improvements of students’ results on measuring rectangle’s area and perimeter. Keyword: Students’ results, Realistic Mathematics Education  Abstrak Penelitian ini dilatar belakangi masih rendahnya ketuntasan minimal mata pelajaran matematika, yang dipengaruhi oleh nilai rata-rata matematika peserta didik yang masih rendah, hal ini dapat terjadi karena pembelajaran matematika selama ini cenderung hanya berupa menghitung angka-angka dan menghafal rumus-rumus, serta bersifat abstrak. Padahal peserta didik yang masih duduk di tingkat Sekolah Dasar pola berpikirnya masih bersifat konkrit. Maka dari itu Peneliti mencoba menggunakan pendekatan Realistic Mathematics Education (RME) dalam pembelajaran matematika yang dapat membawa peserta didik ke hal yang bersifat konkrit. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Subjek dalam penelitian ini yaitu siswa kelas IV SD Negeri 195 Isola Kota Bandung kelas IV A sebanyak 41 siswa yang terdiri dari 17 siswa laki-laki dan 24 siswa,  perempuan. Instrumen pengumpulan data menggunakan pedoman wawancara, pedoman dokumentasi, lembar observasi, pedoman tes, dan angket. Hasil penelitian menunjukan terdapat peningkatah hasil belajar siswa kelas IV Sekolah Dasar Negeri 195 Isola pada pembelajaran matematika  dengan materi keliling dan luas persegi panjang. Kata Kunci:  Hasil Belajar Siswa, Pembelajaran Matematika Realistik